If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 160 + -2x = 34 + 24x Solving 160 + -2x = 34 + 24x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-24x' to each side of the equation. 160 + -2x + -24x = 34 + 24x + -24x Combine like terms: -2x + -24x = -26x 160 + -26x = 34 + 24x + -24x Combine like terms: 24x + -24x = 0 160 + -26x = 34 + 0 160 + -26x = 34 Add '-160' to each side of the equation. 160 + -160 + -26x = 34 + -160 Combine like terms: 160 + -160 = 0 0 + -26x = 34 + -160 -26x = 34 + -160 Combine like terms: 34 + -160 = -126 -26x = -126 Divide each side by '-26'. x = 4.846153846 Simplifying x = 4.846153846
| 17(6c-1)-4=100c+17 | | 3x+22=2x-15 | | [x+4]=3x-5 | | 15x^2+29xy-14y^2=0 | | 45(6+7x)= | | 45(6+7x)=9 | | 2x+3(500-x)=1300 | | .5x+.5x+(x-15)+(x+25)=100 | | 3w-10=9+2W | | .18x=75 | | 5(x+4)-3x=10 | | 4w-12=-2w | | 18-1/22(2x)=9-1/22(x) | | .33x+(x-20)+(x-10)+40=360 | | -23-4=13-8x | | 4/9/8/15 | | 1+(7z-3)=7(-3+5)+2 | | 300=747+(-60) | | Y^2-12y=-31 | | 6x+15x^2=0 | | 5(4x+3)=21 | | -(3x-5)-(7x-6)+12=-3(x-1)-(12x+3)+3 | | 5/6+8/9 | | 5/6*12/17 | | 5-5(4-7x)=0 | | 49-19=5(x-2) | | 109.2/x^3=r | | -3x-2iy=27+i | | 33/8(17/4m+9/4)=2915/32 | | 5-7(8x+2)=4 | | 109.2/r^3=x | | 1/4-5/6= |